Parang sabil the life of Urang Kaya Hadjiyula of Paugan, Parang, Sulu - Isduri, Adjili N. (1999)
Parang sabil is a Tausug concept of defending their freedom/liberty, known as kamaruan, from the colonizers, such as the Spaniards and Americans. This paper will explain the life of Urang Kaya Hadjiyula in defending the freedom or kamaruan of the Muslims against the Spaniards. It will also explain his contribution to Philippine history in general, and the history of the Muslims, in particular. Although the Muslim resistance in Mindanao and Sulu was different from the Philippine Revolution in Luzon and Visayas, it was considered as the most bloody. What was interesting to note in the Moro resistance in Sulu, particularly when the Sultan of Sulu fell into the hands of Spanish authorities in 1571 (de la Costa, 1965), the urang kaya's (middle class) group organized themselves in order to defend their own community from the Spanish invasion. This sentiment is expressed in the saying"Marayawpa muli in bukug ayaw muti'in tikudtikud" (it is better to whiten one's bone in the battle rather than to surrender). Majul (1973) described the Moro resistance to the Spaniards as "the Moro Wars." During these wars, there were many Muslims who were martyred in the battlefield and were called sabil. Sabil is an Arabic term, constructed word from the Qur'anic verse "fry sabiy lillah" (in the way of Allah). T)1e person who involved himself or herself in the act was known as parang sabil. Parang is from a Malay term perang, to mean to kill and be killed. This paper explains what is parang sabil, why it is organized and what is it significance for the Muslims' kamaruwan (honor or dignity). It also explains the role played by Urang Hadjiyula in the history of the Muslims during the Spanish occupation of Jolo.
Includes bibliographical references (pages 29-30).
Keywords: Muslims -- Philippines